Some research results on Bridge health monitoring, maintenance and safety III : special topic volume with invited peer reviewed papers only - Liu, Yang (Of Haerbin gong ye da xue) (Key engineering materials ;, 2014)
The amount of deteriorating bridges is increasing gradually, and the costs of maintenance, repair and rehabilitation of these bridges often far exceed available budgets. To alleviate this issue, the bridge engineering profession continues to take positive steps towards developing more comprehensive bridge monitoring and management systems. This collection of invited papers encompasses some aspects of bridge health monitoring, maintenance and safety. Specifically, it deals with: bridge health monitoring; bridge repair and rehabilitation issues; bridge related safety and other implications. Edit.